DEVELOPMENT OF HOUSEHOLD INFORMATION SYSTEM BASED ON WEBSITE AT THE DIVISION OF COSTUMER’S DATA AND INFORMATION SYSTEM PT. PELABUHAN INDONESIA II (PERSERO) TANJUNG PRIOK - Anie Rose Irawati; Mohamad Faisal Wijaya (Jurnal Komputasi, 2015)
This research is developed a Household Information System based on website. Household information system created for Division of Customer’s Data and Information System in PT. Pelabuhan Indonesia II (Persero) Tanjung Priok. This division handles issues related to the application, network, and multimedia. This information system is created to resolve issues related to submission procedures of damage-handling and submission procedure of new item, so that users can be more efficient in the utilization of time, effort and cost in performing the procedures. This information system is created using PHP programming language. The sequence of process performed is starting from entering data to be submitted, the approval of stakeholders and printing data that have been approved. The result of Black Box testing on the system using Equivalence Partitioning method shows that the system is functioning well and accordance with user requirements. Keywords : Development of Information System, Information System for Household Division, Submission of Damage-Handling